Aging and Veterinary Care of Cats, Dogs, and Horses through the Records of Three University Veterinary Hospitals - Cozzi, Bruno; Ballarin, Cristina; Mantovani, Roberto; Rota, Ada (Frontiers in Veterinary Science, 2017)
The present article examines over 63,000 medical records belonging the Veterinary Hospitals of the Universities of Bologna, Torino and Padova, all in Northern Italy, and relative to dogs (approx. 50,000), cats (approx. 12,000) and companion horses (slightly less than 1,000). The animals of the three species were divided into age classes and categorized per sex into males, females, and neutered individuals. The mean age at visit, and the effects of age classes and category (analyzed via ANOVA) are presented and discussed. The data indicate that many animals are presented to the hospitals either in the early phases of their life (presumably for vaccination and, in cats and dogs, gonadectomy) or in the advanced age (over 10 years in dogs, over 15 years in cats, and over 17 years in horses). The records of very old individuals of the three species are also reported. On the whole, the results suggest that a growing population of mature-to-old domestic carnivores or companion horses reaches ages that were considered exceptional only a few years ago. The data also testifies an evolution in the animal-owner relationship and a renewed respect for the value of life in companion domestic mammals.